Determinant of audit quality: a literature review - Fawziah, Intan Nurbaiti; Hayati, Dian Indah; Hidayatullah, Siti Rahmi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Audit quality plays a crucial role in maintaining the credibility and reliability of financial reporting. This literature review aims to identify and analyze the key determinants that influence audit quality as discussed in prior academic studies. The review categorizes the determinants into auditor-related factors (such as auditor independence, expertise, and tenure), client-related factors (such as company size and complexity), and external factors (such as regulatory environment and audit standards). The findings reveal that audit quality is a multifaceted construct influenced by both internal attributes of auditors and external pressures. By synthesizing findings from various studies, this paper contributes to a better understanding of how different variables interact to affect audit quality, and provides insights for policymakers, auditors, and stakeholders to enhance audit effectiveness